Trends in extreme daily rainfall and temperature indices over South Asia. (24th June 2014) - Sheikh, M. M.; Manzoor, N.; Ashraf, J.; Adnan, M.; Collins, D.; Hameed, S.; Manton, M. J.; Ahmed, A. U.; Baidya, S. K.; Borgaonkar, H. P.; Islam, N.; Jayasinghearachchi, D.; et al.
ABSTRACT Over the last few decades, weather and climate extremes have become a major focus of researchers, the media and general public due to their damaging effects on human society and infrastructure. Trends in indices of climate extremes are studied for the South Asian region using high‐quality records of daily temperature and precipitation observations. Data records from 210 (265) temperature (precipitation) observation stations are analysed over the period 1971–2000 (1961–2000). Spatial maps of station trends, time series of regional averages and frequency distribution analysis form the basis of this study. Due to the highly diverse geography of the South Asian region, the results are also described for some specific regions, such as the island of Sri Lanka; the tropical region (excluding Sri Lanka); the Greater Himalayas above 35°N, the Eastern Himalayas (Nepal) and the Thar Desert. Generally, changes in the frequency of temperature extremes over South Asia are what one would expect in a warming world; warm extremes have become more common and cold extremes less common. The warming influence is greater in the Eastern Himalayas compared with that in the Greater Himalayas. The Thar Desert also shows enhanced warming, but increases are mostly less than in the Eastern Himalayas. Changes in the indices of extreme precipitation are more mixed than those of temperature, with spatially coherent changes evident only at relatively small scales. Nevertheless, most extreme precipitation indices show increases in the South Asia average, consistent with globally averaged results. The indices trends are further studied in the context of Atmospheric Brown Clouds (ABCs) over the region. Countries falling within the ABC hotspot namely Indo‐Gangetic Plain (IGP) have shown a different behaviour on the trends of extreme indices compared with the parts outside this hotspot. IGP has increased temperature and decreased rainfall and tally closely with the actual trends.